2020
DOI: 10.4314/as.v19i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity effect of <i>Kigelia africana</i> aqueous extract on the haematology and histopathology of juvenile Nile Tilapia (<i>Oreochromis niloticus</i>)

Abstract: This study examined the toxicity effect of Kigelia africana on Nile tilapia (Oreochromis niloticus) juveniles. The corresponding effects of this plant extract on the health status of the O. niloticus were similarly studied using their haematological and histopathological profiles. The experiment was carried out at the Hatchery Unit of the Federal University of Agriculture, Abeokuta fish farm. Fish were acclimatized for one week and fed twice daily at the rate of 3% body weight. Water in the culture medium was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The concentration of dissolved oxygen decreased as the concentration increased, resulting in the death of the test fish. This is consistent with the findings of Idowu et al [15] who found that when Oreochromis niloticus was exposed to Kigeliaafricana extract, dissolved oxygen in the water decreased. Akpa et al [16] reported a decrease in dissolved oxygen with increasing concentration when Tilapia zillli was treated with Tephrosia vogelii leaf extract.…”
Section: Discussionsupporting
confidence: 93%
“…The concentration of dissolved oxygen decreased as the concentration increased, resulting in the death of the test fish. This is consistent with the findings of Idowu et al [15] who found that when Oreochromis niloticus was exposed to Kigeliaafricana extract, dissolved oxygen in the water decreased. Akpa et al [16] reported a decrease in dissolved oxygen with increasing concentration when Tilapia zillli was treated with Tephrosia vogelii leaf extract.…”
Section: Discussionsupporting
confidence: 93%
“…Decrease in the value of dissolved oxygen observed implies that the oxygen level in the water has been distorted which might be as a result of predisposition factors of biological living aquatic organisms as opined by Idowu et al (2020) which observed decrease in DO concentration of water used for Oreochromis niloticus culture. Among the innumerable contaminants, pollution by heavy metal in aquatic environments has become a global phenomenon due the higher toxicity and persistence for several decades in the aquatic environment (Thomas and Mohaideen, 2014).…”
Section: Callinectes Danaementioning
confidence: 87%
“…The presence of heavy metals in freshwater ecosystem affects physiological and metabolic activities of fish. Idowu et al (2020) identified Oreochromis niloticus as one of fish affected by heavy metals. this study.…”
Section: Discussionmentioning
confidence: 99%